Neuropathologic basis of in vivo cortical atrophy in the aphasic variant of Alzheimer's disease. (12th September 2019) - Ohm, Daniel T.; Fought, Angela J.; Rademaker, Alfred; Kim, Garam; Sridhar, Jaiashre; Coventry, Christina; Gefen, Tamar; Weintraub, Sandra; Bigio, Eileen; Mesulam, Marek Marsel; Rogalski, Emily; Geula, Changiz
Abstract: The neuropathologic basis of in vivo cortical atrophy in clinical dementia syndromes remains poorly understood. This includes primary progressive aphasia (PPA), a language‐based dementia syndrome characterized by asymmetric cortical atrophy. The neurofibrillary tangles (NFTs) and amyloid‐ß plaques (APs) of Alzheimer's disease (AD) can cause PPA, but a quantitative investigation of the relationships between NFTs, APs and in vivo cortical atrophy in PPA‐AD is lacking. The present study measured cortical atrophy from corresponding bilateral regions in five PPA‐AD participants with in vivo magnetic resonance imaging scans 7–30 months before death and acquired stereologic estimates of NFTs and dense‐core APs visualized with the Thioflavin‐S stain. Linear mixed models accounting for repeated measures and stratified by hemisphere and region (language vs. non‐language) were used to determine the relationships between cortical atrophy and AD neuropathology and their regional selectivity. Consistent with the aphasic profile of PPA, left language regions displayed more cortical atrophy ( P = 0.01) and NFT densities ( P = 0.02) compared to right language homologues. Left language regions also showed more cortical atrophy ( P < 0.01) and NFT densities ( P = 0.02) than left non‐language regions. A subset of data was analyzed to determine the predilection of AD neuropathology for neocortical regions compared to entorhinal cortex in the left hemisphere, which showed that the three most atrophied language regions had greater NFT ( P = 0.04) and AP densities ( P < 0.01) than the entorhinal cortex. These results provide quantitative evidence that NFT accumulation in PPA selectively targets the language network and may not follow the Braak staging of neurofibrillary degeneration characteristic of amnestic AD. Only NFT densities, not AP densities, were positively associated with cortical atrophy within left language regions ( P < 0.01) and right language homologues ( P < 0.01). Given previous findings from amnestic AD, the current study of PPA‐AD provides converging evidence that NFTs are the principal determinants of atrophy and clinical phenotypes associated with AD.